Squamous cell carcinoma predicts worse prognosis in stage IA (≤ 2 cm) non-small cell lung cancer patients following sublobectomy: a population-based study - Jiannan Xu; Kai Zhang; Huiguo Chen; Weibin Wu; Xiaojun Li; Yuanheng Huang; Yonghui Wu; Jian Zhang (Scientific Reports)
Abstract Recent studies recommend sublobectomy as a surgical approach for non-small cell lung cancer (NSCLC) tumors that are 2 cm or smaller. However, it remains unclear whether NSCLC patients with squamous cell carcinoma (SCC) have comparable outcomes to those with adenocarcinoma (ADC) following sublobectomy. To that end, this study aims to compare the survival outcomes between SCC and ADC in patients with stage IA NSCLC (≤ 2 cm) who have undergone sublobectomy. We identified stage IA (≤ 2 cm) NSCLC patients diagnosed with lung squamous cell carcinoma or adenocarcinoma pathology and underwent sublobectomy from the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2020. Overall survival (OS) was determined using the Kaplan–Meier method, and Cox proportional hazards regression was employed to identify risk factors for OS. A total of 9,831 patients diagnosed with stage IA NSCLC (≤ 2 cm) were evaluated. Of these, 2,078 patients met the inclusion criteria, including 1,565 with adenocarcinoma (ADC) and 513 with squamous cell carcinoma (SCC). Notably, SCC was associated with worse overall survival compared to ADC (HR: 2.02, 95% CI: 1.34–3.05, P = 0.03). Subgroup analyses revealed that SCC was comparable to ADC in terms of OS for tumors ≤ 1 cm (HR: 1.22, 95% CI: 0.47–3.18, P = 0.83), while patients with SCC displayed worse OS compared to ADC for tumors > 1 to 2 cm (HR: 2.05, 95% CI: 1.31–3.23, P = 0.002). Cox proportional hazards regression analysis identified female sex (HR: 1.53, 95% CI: 1.08–2.19, P = 0.017), high tumor grade (HR: 1.76, 95% CI: 1.02–3.03, P = 0.011), and SCC (HR: 1.58, 95% CI: 1.08–2.30, P = 0.017) as independent risk factors for OS. In patients with stage IA (≤ 2 cm) NSCLC who underwent sublobectomy, SCC is associated with worse overall survival compared to ADC. Furthermore, being female, having a high tumor grade, and SCC pathology are independent risk factors for OS in these patients.